2010
DOI: 10.1189/jlb.0110025
|View full text |Cite
|
Sign up to set email alerts
|

Indoor insect allergens are potent inducers of experimental eosinophilic esophagitis in mice

Abstract: EE is an emerging disease reported in children and adults of urbanized countries, where indoor insect allergens are major health risk factors. Review of our hospital patient database uncovered that a number of EE patients have hypersensitivity to indoor cat, dog, cockroach, and dust mite allergens. We tested the hypothesis whether inhaled indoor insect allergens are effective inducers of experimental EE. We delivered cat, dog, cockroach, and dust mite allergen extracts intranasally to wild-type and eotaxin-1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 51 publications
6
73
0
2
Order By: Relevance
“…21 Animal models have shown a potential role for aeroallergens eliciting EoE using dust mites, cockroaches, and Aspergillus. 22,23 Rayapudi et al found in 236 children, 38% had sensitizations to indoor allergens, particularly cockroach and dust mite. 23 Gonsalves et al studied 50 adults and 30% had isolated positive SPT to aeroallergens, most commonly to pollen and dust mite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Animal models have shown a potential role for aeroallergens eliciting EoE using dust mites, cockroaches, and Aspergillus. 22,23 Rayapudi et al found in 236 children, 38% had sensitizations to indoor allergens, particularly cockroach and dust mite. 23 Gonsalves et al studied 50 adults and 30% had isolated positive SPT to aeroallergens, most commonly to pollen and dust mite.…”
mentioning
confidence: 99%
“…22,23 Rayapudi et al found in 236 children, 38% had sensitizations to indoor allergens, particularly cockroach and dust mite. 23 Gonsalves et al studied 50 adults and 30% had isolated positive SPT to aeroallergens, most commonly to pollen and dust mite. 16 The pathogenesis of EoE is still not entirely clear.…”
mentioning
confidence: 99%
“…For example, adult patients seem to present a higher proportion of IgE-mediated positive allergy results than children in whom sensitization to both indoor and outdoor antigens have been documented [20,25]. Both types of antigens have been demonstrated to cause experimental EoE [26]. As noted above, seasonal variation in the diagnosis and severity of EoE has been reported for both children [27] and adults [16], and after that, some researchers have posed that airborne-antigens may trigger and help to maintain EoE, even when no clinical human trials have been conducted to undoubtedly demonstrate air-borne allergens as EoE triggers.…”
Section: Allergy Study Results In Eoe Patientsmentioning
confidence: 99%
“…Obserwację tę potwierdziło wielu innych badaczy -diagnostyka w kierunku alergii pokarmowej należy obecnie do standardu diagnostycznego EoE, ale jak wskazuje ogól-noświatowe badanie gastrologów, obecnie 77% dzieci i tylko 16% dorosłych z EoE jest badanych w kierunku alergii pokarmowej [1,2,7,11]. Na modelach eksperymentalnych udowodniono, że alergeny kurzu domowego i pleśni mogą również powodować powstanie nacieków eozynofilowych w przełyku [12]. Jak wskazują badania z ostatnich lat, nieliczni chorzy, u których nie udaje się potwierdzić uczulenia, lokalnie -w błonie ślu-zowej przełyku -syntetyzują IgE [13].…”
Section: Wstępunclassified